PENGEMBANGAN SUMBER DAYA MANUSIA, PELATIHAN DAN KOMPETENSI TERHADAP KINERJA KARYAWAN - Sri Langgeng Ratnasari; Desi Ulfah (JURNAL DIMENSI, 2021)
Research on employee performance is still an interesting topic in the field of human resource management. The purpose of this study was to analyze the effect of Human Resource Development on employee performance, analyze the effect of Training on employee performance, analyze the effect of competence on employee performance, and analyze the effect of human resource development, training and Competence on Employee Performance. The population of this research is the employees of PT. Mutiara Jaya Batam as many as 50 employees. The research sample of 50 respondents using census sampling techniques. Data collection is done by questionnaire. This study uses multiple linear regression analysis tools. The results showed that Human Resource Development significantly affected employee performance, Training significantly affected Employee Performance, and Competence had no significant effect on Employee Performance, and Human Resource Development, Training, and Competence affected Employee Performance. The variables of Human Resource Development, Training and Competence are able to explain the Employee Performance variable of 72.1% and the remaining 27.9% are explained by other variables not included in this study.